Analisis Struktur Kinerja Dan Kluster Industri Unggulan - Fitri Elmawati; Habibur Rohman; Muhammad Yasin (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
Abstract. This change in the structure of the agriculture-based economy towards industry has resulted in many benefits to be gained from this change. The existence of regional superiority can indicate added value and high productivity due to the built competitiveness. This is related to the industrial sector which has a close relationship with the economic development of a country because the progress of the manufacturing industry sector is one indicator of a country's economic success. The manufacturing industry is an economic driving tool for a country in its efforts towards a better and more stable economy. The development of a strategic industry because it has great potential to develop in the future. Which is able to make industrial clusters a driver of Indonesia's economic growth